DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE INFORMATICS TEACHERS: A TIMELY IMPERATIVE (Neo Science Peer Reviewed Journal, 2023)
In an era characterized by rapid technological advancement and an unprecedented reliance on digital literacy, the role of informatics teachers has become paramount in shaping the next generation's technological proficiency. This scientific article delves into the critical issue of developing the professional competence of future informatics educators, recognizing it as an urgent and pivotal endeavor. The summation of this research aims to shed light on the multifaceted dimensions of this challenge and provide actionable insights for academia, educational policymakers, and practitioners alike.